Campus Habituation and Digital Culture in Strengthening Communication Ethics - Saddam, Saddam; Hermanto, Fredy; Wisnuwardana, I Gede Wayan; Mirzachaerulsyah, Edwin; Tanggur, Femberianus Sunario; Garba, Malami Muhammad; Nuryanti, Nuryanti; Rahmandari, Ismi Arifiana (International Journal of Social Learning (IJSL), 2025)
This study examines how integrating digital culture values in campus habituation strengthens students’ digital communication ethics as social capital. Using a qualitative descriptive method in Mataram City, data were collected from students, lecturers, staff, and campus leaders through interviews and observations. Findings reveal that students recognize the importance of digital values such as netiquette, digital literacy, and digital citizenship. However, the implementation of these values remains inconsistent and unstructured. Ethical awareness in digital communication varies among students, especially regarding personal social media use. Despite these challenges, digital platforms like WhatsApp and Instagram support the development of bonding and bridging social capital through trust-building and collaboration. The study suggests the need for structured campus policies, regular digital ethics training, curriculum integration, and digital communities to foster ethical digital behavior in academic settings.